ENGLISH LEARNING MANAGEMENT IN THE ERA OF COVID-19 AT YOUNG LEARNER EDUCATION DEPARTMENT OF STKIP BINA INSAN MANDIRI - Norma Diana Fitri; Sulistiyani . (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Abdurachman Saleh Situbondo, 2021)
As a Teaching and Education College, STKIP Bina Insan Mandiri, especially the English Learning management at young learner departement that has the courage to take steps to make online learning an opportunity to transform education. There are several steps that can be a collective reflection in improving the education system, especially related to online learning. Online learning usually, the instructors are in separate locations so that it requires an interactive telecommunication system to connect the two and the various resources needed in it. Electronic learning (e-learning) or online learning (online) is part of distance education that specifically combines electronic technology and technology for English learning. In qualitative research here, it is related for making notes that really need to be done in order to make data analysis. Note making can be done while conducting interviews or while still conducting interviews, observations, and documentation. By using the documentation, method means collecting data by recording existing data. Documents can be in the form of writings, pictures, or works of someone. So, online learning used as an effort to learn from lecturers, which is to focus more on efforts to transfer knowledge and skills for the students. This policy can also encourage students to be more innovative and creative in learning (students centered learning) especially at young learner departement STKIP Bina Insan Mandiri. The physical encounter will not be abandoned even though the advancement of virtual and digital technology is getting thicker. Even though the Covid-19 outbreak will be last for a long time, we must think about patterns and methods of physical and social learning that are safe for everyone. The development of communication and digital technology has a significant role that academics can make the wide using to look a brighter future, especially at STKIP Bina Insan Mandiri, for Young Learner Departement in English Language teaching.